Forensic accounting : how to investigate financial fraud - Thornhill, William T., 1926- (Kuala Lumpur : Synergy Books International, 1995)
Escalating levels of white collar crime in all branches of business, government, and society call for a new breed of investigator - one who is well versed in auditing, analysis, and internal evaluation. More and more, courts are relying upon accountants to provide information that may be used as evidence in a civil or criminal investigation of an organization's compliance with the laws, regulations, and statutes designed to reduce the risk of crime.
Forensic Accounting provides straightforward coverage of principles and practices of forensic accounting and the services that can be provided by forensic accountants; the six basic steps for evaluating internal controls; the steps of a typical fraud investigation, the roles of those involved, and'checkpoints' to determine whether it is correct to continue or discontinue the investigation; the difference in the approach to'on-book' fraud as opposed to'off-book' fraud; major categories of fraud and how to detect fraud; and the importance of using the latest technology to develop pertinent facts and supporting data. Author William Thornhill also shows how members of management, law-enforcement authorities, and the legal profession can effectively utilize the services of the forensic accountant.
Ch. 1. Overview of Accounting -- Forensic and General -- Ch. 2. Services That Can Be Provided by Forensic Accountants -- Ch. 3. Skills Required of the Forensic Accountant -- Ch. 4. Four Phases of a Forensic Accounting Review -- Ch. 5.'On-Book' Accounting and Financial Statement Fraud -- Ch. 6.'Off-Book' Accounting and Financial Fraud -- Ch. 7. Computers and Computer Fraud -- Ch. 8. Investigation -- Ch. 9. Gathering Evidence -- Ch. 10. Interviewing and Interrogation -- Ch. 11. Essential Theories and Principles of Fraud -- Ch. 12. Principles of Accounting, Financial Statements, and Financial Analysis -- Ch. 13. Evaluating Organization and Internal Controls -- Ch. 14. Criminology -- Ch. 15. Litigation Services -- Ch. 16. Where is Forensic Accounting Going from Here?.
Originally published: Burr Ridge, Ill. : Irwin Professional Pub., [1995].
Includes bibliographical references and index.
Keywords: Forensic accounting -- United States; Evidence, Expert -- United States; Accounting -- United States